PCSK9 Gene E670G Polymorphism and Coronary Artery Disease: An Updated Meta-Analysis of 5,484 Subjects - Li, Yan-yan; Wang, Hui; Yang, Xin-xing; Geng, Hong-yu; Gong, Ge; Lu, Xin-zheng (Frontiers in Cardiovascular Medicine, 2020)
Objective: Research has shown a possible relationship between the E670G polymorphism of the proprotein convertase subtilisin/kexin type 9 (PCSK9) gene and an increased risk of coronary artery disease (CAD). However, there is no clear consensus on the subject due to conflicting results in the literature. The current meta-analysis was performed to better elucidate the potential relationship between the PCSK9 gene E670G polymorphism and CAD. Methods: 5,484 subjects from 13 individual studies were included in the current meta-analysis. The fixed or random effect models were used to evaluate the pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs). Results: The current meta-analysis found a significant association between PCSK9 gene E670G polymorphism and CAD under allelic (OR: 1.79, 95% CI: 1.42-2.27, P=1.00×10-6), dominant (OR: 2.16, 95% CI: 1.61-2.89, P=2.22×10-7), heterozygous (OR: 2.02, 95% CI: 1.55-2.64, P=2.47×10-7), and additive genetic models (OR: 1.92, 95% CI: 1.49-2.49, P=6.70×10-7) . Conclusions: PCSK9 gene E670G polymorphism was associated with an elevated risk of CAD, especially in the Chinese population. More specifically, carriers of the G allele carriers of the PCSK9 gene may be predisposed to developing CAD.